Bone exostosis lesions in distal limb of equines (17 cases; 10 horses, 7 donkeys): A clinical study - Mohammed A. Noby (South Valley University, 2021)
Lameness is an important clinical sign for the problems of locomotor system. When, visual inspection and diagnostic analgesia are not enough for reaching out the accurate diagnosis of the lesion, diagnostic imaging including radiology helps to determine the problem in a specific area. This study investigated the role of radiography as a crucial step for clinical diagnosis of bone exostosis lesions in equines. Between July 2019 and December 2020, seventeen animals were involved in this study 10 horses and 7 donkeys. These animals (age, 4.1±3.8 years; weight, 199±98 Kg) were suffered from lameness with prominent bone exostosis on the distal limb, then were subjected to radiographic examination with lateromedial and dorsopalmar/dorsoplantar views. The most detected cases were more prevalent in the fore limb (76.5%) than the hind limb (23.5%). The most prevalent lesions recorded in this study were ring bone (9 cases; 52.9%), Degenerative joint disease of the carpal joint and sore shins (3 cases; 17.64%) for each, and then bone spavin and side bone were the lowest prevalent one (1 case; 5.88%) for each. There was no treatment for all cases except sore shins which was improved thoroughly by topical iodine compounds with systemic administration of phenylbutazone. X-ray radiography is still beneficial for equine industry especially in the lesions related to the joints and bone exostosis that appeared on the distal limb.